2021
DOI: 10.1038/s41438-021-00500-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular functions of nitric oxide and its potential applications in horticultural crops

Abstract: Nitric oxide (NO) regulates plant growth, enhances nutrient uptake, and activates disease and stress tolerance mechanisms in most plants, making NO a potential tool for use in improving the yield and quality of horticultural crop species. Although the use of NO in horticulture is still in its infancy, research on NO in model plant species has provided an abundance of valuable information on horticultural crop species. Emerging evidence implies that the bioactivity of NO can occur through many potential mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 211 publications
(106 reference statements)
0
26
0
Order By: Relevance
“…Nitrosative stress caused by biotic and abiotic factors is a major challenge to plant survival ( Corpas et al, 2021 ; Sun et al, 2021 ). The levels of GSNO, a bioactive form of NO, are known to be regulated by GSNOR ( Lee et al, 2008 ; Guerra et al, 2016 ), and plants lacking the enzyme show multiple phenotypic alterations, indicating that tightly controlled RNS levels are crucial for proper plant growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrosative stress caused by biotic and abiotic factors is a major challenge to plant survival ( Corpas et al, 2021 ; Sun et al, 2021 ). The levels of GSNO, a bioactive form of NO, are known to be regulated by GSNOR ( Lee et al, 2008 ; Guerra et al, 2016 ), and plants lacking the enzyme show multiple phenotypic alterations, indicating that tightly controlled RNS levels are crucial for proper plant growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…The overall positive effects of NO against GLY-mediated toxicity on the growth and antioxidant response of tomato plants were also evident in the flowering process. As reviewed by Sun et al [61], NO was already proved to benefit plant reproductive traits, inducing the expression of several flowering-related genes. Moreover, although the total number of produced tomatoes was still lower than that of the CTL, fruits' average fresh mass was improved and remained identical to unexposed plants.…”
Section: Gly-mediated Effects On Crop Productivity Are Partially Prevented By the Co-application Of Nomentioning
confidence: 99%
“…Moreover, although the total number of produced tomatoes was still lower than that of the CTL, fruits' average fresh mass was improved and remained identical to unexposed plants. Indeed, NO application has been found to modulate fruit quality features, contributing for a better firmness and to delay fruit ripening, by inhibiting ethylene biosynthesis [61].…”
Section: Gly-mediated Effects On Crop Productivity Are Partially Prevented By the Co-application Of Nomentioning
confidence: 99%
“…Nitric oxide is a small, gaseous signaling molecule that has been studied for decades in mammalian cells. Recent research findings have shown that NO regulates plant growth, enhances nutrient uptake, and activates stress tolerance mechanisms in most plants (Sun et al, 2021). NO is a negative regulator of the chlorophyll (Chl) catabolic pathway and positively maintains the stability of thylakoid membranes during leaf senescence (Liu and Guo, 2013).…”
Section: Introductionmentioning
confidence: 99%